Vera - odgovor na osamljenost sodobnega človeka v luči osnovnega bogoslovja - Trontelj, Nik (Bogoslovni vestnik, 2023)
The development of online forms of interpersonal communication in the digital age has plunged many individuals into social isolation and loneliness, despite the unlimited offer for establishing contacts. With the emergence of new means of communication in the modern world, authentic interpersonal relationships are ironically weakening. In the article, we argue that faith in God alone, which is born in relation to another person, can give meaning to human life. Being faithful means overcoming self isolation and going »out of yourself« towards the other. The answer to »digital loneliness« is faith, which manifests the relationship to God in love for another person and fully realizes the individual as a person. Our thinking is grounded in the theological teachings of selected lecturers of fundamental theology who have taught at the Faculty of Theology in Ljubljana within the past fifty years.
Keywords: digital age; digitalna doba; faith; fundemental theology; interpersonal relationships; loneliness; medosebni odnosi; osamljenost; osnovno bogoslovje; vera